'Home' Concept in Adolescents in a Military Housing Sphere - Diana Wahyu Pratiwi; Purwanita Setijanti; Sarah Cahyadini (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
Adolescence is a period of transition of an individual from childhood to adulthood. At this time, individuals are encouraged to have excitement in exploring themselves to find identity. Their sphere is the first place that accommodates the daily lives of adolescent. Adolescent sphere conditions can shape the identity of adolescents. Adolescent feel comfortable and have ease in forming identity if they feel they are in the right environment. The right sphere here is meant to be a adolescent that can form the concept of 'home'. The concept of 'home' is the achievement of a sphere from the perspective of residents who feel comfortable so that they can form (1) memories, fulfill (2) privacy, form (3) habits or subsquent behavior and can create (4) the desire to return to live. A sphere with the concept of 'home' for adolescents certainly provides freedom for adolescents to explore themselves, but adolescent who live in military residential areas face different things. In this sphere area there are binding rules that must be obeyed by all residents, as well as adolescent. This research was conducted using a mixed method by conducting interviews and data processing with a word processing application to find keywords from adolescents in describing their sphere. The words were then coded, to find the concept of 'home' for the adolescent living in the military complex.